The effect of hyperthermia on the induction of cell death in brain, testis, and thymus of the adult and developing rat - Khan, Vania R. (Cell Stress Society International, 2002)
Stressful stimuli can elicit 2 distinct reactive cellular responses, the heat shock (stress) response and the activation of cell death pathways. Most studies on the effects of hyperthermia on the mammalian nervous system have focused on the heat shock response, characterized by the transient induction of Hsps, which play roles in repair and protective mechanisms. This study examines the effect of hyperthermia on the induction of cell death via apoptosis, assayed by terminal deoxynucleotidyl transferase–mediated deoxyuridine triphosphate nick-end labeling and active caspase 3 cytochemistry, in the adult rat brain, testis, and thymus. Results show that a fever-like increase in temperature triggered apoptosis in dividing cell populations of testis and thymus, but not in mature, postmitotic cells of the adult cerebellum. These differential apoptotic responses did not correlate with whole-tissue levels of Hsp70 induction. We further investigated whether dividing neural cells were more sensitive to heat-induced apoptosis by examining the external granule cell layer of the cerebellum at postnatal day 7 and the neuroepithelial layers of the neocortex and tectum at embryonic day 17. These proliferative neural regions were highly susceptible to hyperthermia-induced apoptosis, suggesting that actively dividing cell populations are more prone to cell death induced by hyperthermia than fully differentiated postmitotic neural cells.